تحليل الأخطاء في نطق الأصوات اللثوية لدى طلاب الجامعة الإسلامية العالمية بماليزيا Analysis of errors in the pronunciation of gingival sounds among students of the International Islamic University in Malaysia. - Redzuan, Nuraziani; Mohammad Alramadeen, Mohammad Khalil (Kulliyyah of Languages & Management (KLM), International Islamic University Malaysia, 2022)
Learning phonetics is an important aspect of life that every person needs to learn at an early age, and one of the important branches of phonology is learning letter exits. Muslims who adhere to the Qur’an and the Sunnah need to know the basics of the letter exits because when each letter is pronounced, it will affect the meaning of each word in the Quran. Researcher found that there are problems with the pronunciation of gingival letters among students. Hence, this study is trying to analyse of errors in the pronunciation of gingival sounds (th, dh, z) focuses on the students at International Islamic University Malaysia Pagoh Campus. This study seeks to know the common errors in the pronunciation of these sounds and the factors that lead to this problem. To answer the research questions, researcher use descriptive analysis research methods. The researcher prepared some excerpts of Quranic verses containing gingival letters to be given to sixteen study samples of different courses from Kulliyah of Languages and Management to evaluate their pronunciation as well as conduct the interviews to assess the second question of the research which is the factors that caused errors in their pronunciation in depth. الملخص يعد علم الأصوات جانبًا مهمًا من جوانب الحياة ويحتاج إلى تعلمه كل إنسان في سن مبكرة. يحتاج المسلمون الذين يلتزمون بالقرآن والسنة إلى معرفة أساسيات مخارج الحروف بدقة لأنه عند نطق كل حرف، سيؤثر ذلك على معنى كل كلمة في القرآن. ووجدت الباحثة أن هناك مشاكل في نطق الأصوات اللثوية لدى الطلاب. لذلك، يحاول هذا البحث في تحليل الأخطاء في نطق الأصوات اللثوية (ث، ذ، ظ) مركزّاً على طلاب الجامعة الإسلامية العالمية سعياً إلى معرفة الأخطاء الشائعة في نطق الأصوات اللثوية والكشف عن عوامل تؤدي إلى هذه المشكلة. للإجابة على أسئلة البحث، تستخدم الباحثة المنهج الوصفي التحليلي. أعدت الباحثة بعض آيات قرآنية تحتوي على الأصوات اللثوية تعطى لستة عشر عينة دراسية من أقسام مختلفة في كلية اللغات والإدارة لتقييم نطقها وإجراء المقابلات للحصول على الإجابة عن السؤال الثاني للبحث وهو العوامل التي تسببت أخطاء في النطق بمزيد من التفصيل.